Identities on solutions of the wave equation in the enveloping algebra of the conformal group; Theoretical and Mathematical Physics; Vol. 83, iss. 1 - Bagrov V. G.; Samsonov B. F.; Shapovalov A. V. Aleksandr Vasilyevich; Shirokov I. V. (1990, 1990)
Title screen